Crystallographic structure determination and analysis of a potential short-chain dehydrogenase/reductase (SDR) from multi-drug resistant Acinetobacter baumannii. - Seyed Mohammad Ghafoori; Soha Abdollahpour; Paniz Shirmast; Jade K Forwood (PLoS ONE, 2023)
Bacterial antibiotic resistance remains an ever-increasing worldwide problem, requiring new approaches and enzyme targets. Acinetobacter baumannii is recognised as one of the most significant antibiotic-resistant bacteria, capable of carrying up to 45 different resistance genes, and new drug discovery targets for this organism is an urgent priority. Short-chain dehydrogenase/reductase enzymes are a large protein family with >60,000 members involved in numerous biosynthesis pathways. Here, we determined the structure of an SDR protein from A. baumannii and assessed the putative co-factor comparisons with previously co-crystalised enzymes and cofactors. This study provides a basis for future studies to examine these potential co-factors in vitro.